A different indication of pisphosphonates: Bone marrow edema. (27th January 2023) - Çalışkan, Mustafa; Kızılgül, Muhammed; Bostan, Hayri; Çakal, Erman
Abstract: Introduction: Bone marrow edema (BME) is an uncommonly diagnosed, reversible condition most often affecting the hip of middle-aged men. BME is characterized clinically by the onset of disabling bone pain, usually at a single skeletal site, generally in the lower limbs and most often the hip. Diagnosis is often delayed. The increased bone turnover and low bone mineral density may indicate a potential role for bisphosphonate therapy in BME. There is some evidence of the successful use of intravenous bisphosphonates in the treatment of BME of the hip. We aimed to present two cases of BME that were successfully treated with bisphosphonates. Clinical Case: 1: A 41-year-old male patient presented with left inguinal pain. His past medical history was unremarkable. The visual analog scale (VAS) was 8–9. On physical examination, there was a limited range of motion (ROM) on the left hip. Laboratory results were within normal limits. Non-contrast MRI revealed signal intensity changes consistent with BME in the left femoral head and neck of the femur, which was hypointense in T1W sections and hyperintense in T2W sections. With assisted mobilization, 3 mg IV ibandronic acid, calcium and vitamin D replacement was started. Pain control was achieved one week after bisphosphonate infusion. Complete resolution of bone marrow edema was seen in the MRI taken 2 months later (Figure 1 ). Bisphosphonate treatment with alendronate was completed for one year. Figure 1. Signal intensity changes consistent with hyperintense bone marrow edema are observed in T2W sections in the left femoral head and femoral neck location (A), which regressed in the follow-upstudy (B). Clinical Case: 2: A 59-year-old male patient presented with right hip pain that limits his walking. He was diagnosed with BME and avascular necrosis as a result of clinical and radiological evaluation in the center he applied and he underwent a right femoral core decompression operation. He was evaluated in our clinic due to ongoing pain and limitation of movement 5 months after the operation. On physical examination, there was limited ROM on right hip. All the results of laboratory tests were normal. MRI revealed signal changes consistent with bone marrow edema in the right femoral head and neck of the femur, which was hypointense in T1W sections and hyperintense in T2W sections. With assisted mobilization, 3 mg IV ibandronic acid, calcium and vitamin D replacement was started. Pain control was achieved 10 days after bisphosphonate infusion, and he returned to working life 1 month later. Complete resolution of the BME was observed in MRI performed 10 weeks later. Completion of the bisphosphonate treatment with alendronate for 1 year was planned. Conclusion: The hip is the most frequently involved joint, with diffuse BME pattern in the femoral head and intertrochanteric region observed on MRI. BME may be a precursor to avascular necrosis when the diagnosis is delayed or the treatment is not well managed. Therefore, optimal timing of medical intervention is very important. Treatment with bisphosphonates is an effective and safe treatment. Additionally, providing early mobilization may prevent the risk of avascular necrosis and the workforce loss.